[(Z)-Isopropoxy(4-nitrophenylimino)methanethiolato-κS](tricyclohexylphosphine-κP)gold(I) - Ho, Soo Yei (International Union of Crystallography, 2009)
In the title compound, [Au(C(10)H(11)N(2)O(3)S)(C(18)H(33)P)], the gold(I) atom is linearly coordinated within a SP donor set. The distortion from linearity [S—Au—P = 177.54 (3)°] can be traced to an intramolecular Au⋯O contact of 3.009 (3) Å. In the crystal, layers of molecules are stabilized by a combination of C—H⋯O and C—H⋯π interactions.